2018
DOI: 10.20546/ijcmas.2018.711.193
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Efficacy of Pseudomonas fluorescens Against the Root-Knot Nematode (Meloidogyne incognita) in Tomato Plant

Abstract: parasitic nematodes (Oostendrop and Sikora, 1990; Muthulakshmi et al., 2010). A pot culture study was conducted by Jonathan and Umamaheswari (2006) to assess the biocontrol potential of endophytic bacteria. A significant reduction in nematode population was observed in the combined treatment of EPB 5 + 31. Munif et al., (2001) reported that the endophytic bacterium Pseudomonas pullida

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Specifically, previous studies have reported that T. viride MTCC No. 167, T. asperellum T-12, and T. harzianum T-78 were potential biological agents against M. incognita [22][23][24][25]. Furthermore, a few other microorganisms such as S. rubrogriseus, B. subtilis, P. putida and P. fluorescens have been employed in controlling M. incognita [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, previous studies have reported that T. viride MTCC No. 167, T. asperellum T-12, and T. harzianum T-78 were potential biological agents against M. incognita [22][23][24][25]. Furthermore, a few other microorganisms such as S. rubrogriseus, B. subtilis, P. putida and P. fluorescens have been employed in controlling M. incognita [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the present assessment, both the species of Trichoderma caused reductions in root galling, egg masses, fecundity, and reproductive factor of M. javanica. Many earlier studies have shown good control of root-knot nematodes and many plants pathogenic fungi by different species of Trichoderma [65][66][67][68]. Trichoderma species being omnipresent dwell freely in all types of soils and are frequently found in root ecosystems of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma species are commonly found in root ecosystems, which develop symbiotic relationships with different kinds of crops, by colonizing root surfaces and enter the epidermis to enhancing root growth, increasing production and improved nutrients uptake (Kiriga et al, 2019). Trichoderma have provided excellent control method against root-knot nematodes in previous studies (Sonkar et al, 2018). Al-Hazmi and Javeed (2016) reported that T. harzianum and T. viride suppressed nematode multiplication and root galling and increased growth of tomato plants.…”
Section: Discussionmentioning
confidence: 99%